Diferencias motoras en atletas cadetes de taekwondo según nivel competitivo - De la Fuente, A.; Gómez-Landero Rodríguez, L. A. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2019)
The aim of this study was to determine the differences between Taekwondo cadet athletes belonging to different competition levels in terms of anthropometry, legs power, flexibility and reaction time. Twenty male athletes were analysed, divided in two groups: national medallist and non-national medallist. Data of every athlete`s anthropometric measurements, reaction speed ability, leg power and hip ROM (range of movement) were taken. Medallist athletes showed significantly lower values for height, arm span, foot reaction time (dominant and non-dominant) and non-dominant hand reaction time; and higher values for leg length, passive hip flexion, active hip abduction and passive hip abduction in ROM tests. Slight differences observed between medallists and non-medallists in leg power (CMJ), body fat (S skinfolds) and active hip flexion do not agree with previous studies. Knowing this information could be interesting for coaches in order to carry out talent detection programs.